ANALISIS PEMBIAYAAN PEMBANGUNAN PERUMAHAN PURI CEMPAKA MAS DALUNG KUTA UTARA KAB. BADUNG - Dharma Warsika, I Putu (Jurnal Ilmiah Teknik Sipil; Jurnal Ilmiah Teknik Sipil, Vol. 18, No. 1, Januari 2014, 2016)
Bali Indonesia as a tourism destination is one area that has a steeper rate of economic growth. To welcome the many needs of residential, deemed necessary by PT Puri Darma Sejati to help meet the needs of the community will be huge demand for residential. Along the way , of course discovered the problem whether a housing development should be feasible . Based on the above issues will be addressed in this research project is to analyze financial Park Housing Development Sastraloka used financial analysis is based on monthly financial reports such as cash flow analysis and analysis of bank capital loan, to be known financial measures to be taken by the management as well as to analyze the feasibility with the Net Present Value, Internal Rate of Return ( IRR ) and Benefit Cash Ratio ( BCR ). From the analysis, the financial activities of PT Puri Darma Sejati on this project include: initial capital used in this project comes from the rest of the cash business the previous year. In November 2010 until January 2012 the necessary steps in the form of bank loans due to the financial capital of the company and the sale is insufficient spending for the month. Returns principal bank loans made in May 2011 to February 2012 by using mortgage disbursement. Initial payback company at the end of the activities carried out in November 2012.  At a financial analysis has been done with the Net Present Value ( NPV ) obtained positive results of Rp. 9.101.367.667,77 ( NPV > 0 ). For the calculation of Benefit Cost Ratio ( BCR ) obtained a value of 1.368is greater than one ( BCR > 1 ). Internal Rate of Return ( IRR ) NPV( - ) index not found.
Keywords: Financial Analysis, Feasibility, Financial Activities